2017
DOI: 10.1155/2017/4280583
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Middle Ear Infections and Associated Risk Factors in Children under 5 Years in Gasabo District of Kigali City, Rwanda

Abstract: Middle ear infections are common in children, and delay in diagnosis and treatment may result in complications such as delays in speech and language development and deafness. The aim of this study was to determine the prevalence and care seeking behaviour for middle ear infections in children under five years in Kigali city. We conducted a cross-sectional study among 810 children aged 6–59 months in Gasabo district of Kigali city, Rwanda. The prevalence of middle ear infections was 5.8%, of whom 4% had chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 35 publications
4
15
4
2
Order By: Relevance
“…In our study population, however, otorrhoea affected both children with an uneducated or an educated family background, as 21% of the children's parents/primary caregivers had no or only primary education while 16% had university-level education. Unlike in a recent African study from Mukara et al from Rwanda [10], we did not observe a statistical association between length of otorrhoea and education level in the family. In Angola, improved knowledge of AOM and CSOM is likely needed across the entire population regardless of education level.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study population, however, otorrhoea affected both children with an uneducated or an educated family background, as 21% of the children's parents/primary caregivers had no or only primary education while 16% had university-level education. Unlike in a recent African study from Mukara et al from Rwanda [10], we did not observe a statistical association between length of otorrhoea and education level in the family. In Angola, improved knowledge of AOM and CSOM is likely needed across the entire population regardless of education level.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, however, the median time of U-5 children to seek consultation was shorter (median 1 to 3 months) than the findings from Tiedt et al from South Africa, where most U-5 children suffered from symptoms for 18 months [21]. In addition to difficulties in seeking and accessing care in Africa, the long duration of otorrhoea also suggests that both AOM and CSOM are not well recognised in Africa [10,22]. In Africa, CSOM is often associated with poverty [8,23].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study conducted in Rwanda describing reasons for late care seeking for CSOM. This is a common condition and comparative studies show that majority of people with long standing CSOM or those with ear infections globally reside in developing countries [ 2 , 16 ] and specifically in rural areas [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Sub-Saharan Africa, these range from 0.4% to 4.2%. [28] Overall, CSOM is considered to be the most common cause of persistent mild to moderate HL among children and young people in developing countries and causes HL in more than 50% of those affected. [29] Smith WA et al, (1996) found that while 64% of schoolchildren with CSOM had HL, only 3.4% of children without CSOM had HL.…”
Section: Primary Ear and Hearing Care (Pehc)mentioning
confidence: 99%